FORMATION OF THE RELIGIOUS CHARACTER OF STUDENTS BASED ON RELIGIOUS EDUCATION IN SMK NEGERI 2 MALANG - Ridwan, Ridwan; Tobroni, Tobroni; Khozin, Khozin (EDUKASI: Jurnal Pendidikan Islam, 2018)
The focus of this research is how the character of students religiosity in SMK Negeri 2 Malang,, the values of religuised characters instilled based on religious education, and the formation method of character religious students in SMK Negeri 2 Malang. This research used a qualitative approach. With this type of case study research. The collection of data through in-depth observation, interviews and documentation studies. Research informants are headmaster of SMK N 2 Malang, Islamic teacher, religious teacher for non Muslim, general teachers, administrative departments (TU), Muslim students, and non Muslim students. This research used purposive sampling and with snowball sampling technic. Checking the validity of the data, Condensation, data display, and conclusion drawing / verifications. The research showed that (1). The religiosity character of students in SMK Negeri 2 Kota Malang is highly variable, one of the background behind is their family, Then the religious character of students there are three categories, including very religious, religious and less of religious, (2). The process of implementation values of religious characters to students based on religious education at SMK Negeri 2 Malang are includes: Greetings, shaking hands, reading Asmaul Husna every morning, praying together before and after lessons, Dhuha prayers, zuhr prayer in congregation, Istighosah, Friday Prayers, deepening of the Quran every Saturday, (3). Methods of forming religious character include: exemplary/habituate method, question and answer method, discourse method, and problem solving method.